2013
DOI: 10.5858/arpa.2012-0151-cr
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Philadelphia Chromosome–Positive Chronic Myelogenous Leukemia With Trisomy 19 Presenting With Megakaryoblastosis and Myelofibrosis

Abstract: Initial identification of chronic myelogenous leukemia is very important since targeted therapy leads to life-saving remission. Rarely, chronic myelogenous leukemia presents with an unusual picture, making the diagnosis challenging. We describe such a case of chronic myelogenous leukemia in blast crisis in a previously healthy 61-year-old woman. The patient presented with fever, myalgias, and night sweats and was first worked up for an infectious etiology. Because of persistent anemia, a bone marrow biopsy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Chromosome 19 abnormalities may be present in any of these entities and may also occur as a secondary abnormality with additional recurrent abnormalities such as t(9;22), trisomy 21, t(1;22), as well as numeric abnormalities and deletions in MDS [ 25 ]. On the other hand, an isolated trisomy 19 is a marker of myeloid disorders most commonly associated with AML-M7 both in cases that are de novo and secondary to evolved MDS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome 19 abnormalities may be present in any of these entities and may also occur as a secondary abnormality with additional recurrent abnormalities such as t(9;22), trisomy 21, t(1;22), as well as numeric abnormalities and deletions in MDS [ 25 ]. On the other hand, an isolated trisomy 19 is a marker of myeloid disorders most commonly associated with AML-M7 both in cases that are de novo and secondary to evolved MDS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, small lymph nodes (1-2 cm in diameter) remained in the neck and supraclavicular after 4 courses of chemotherapy. Therefore, the patient was treated with 2 courses of BEACOPP (bleomycin, 15 mg, day 8; etoposide, 200 mg, days 1-3; doxorubicin, 80 mg, day 1; cyclophosphamide, 1,200 mg, day 1; vincristine, 4 mg, day 8; procarbazine, 700 mg, days 1 and 15; and prednisone, 80 mg, days 1-14) combined with local radiotherapy (2 Gy, days [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Residual lesions were not observed on CT scans, and a BM biopsy demonstrated recovery of hematopoiesis and a disappearance of fibrosis.…”
Section: Case Reportmentioning
confidence: 99%
“…Clinical manifestations of myelofibrosis include cytopenias, profound splenomegaly, bone pain, night sweats, weight loss, and fatigue (4). Secondary MF (SMF) is often observed in a number of hematological malignancies, including acute megakaryoblastic leukemia (5), chronic myeloid leukemia (6) and hairy cell leukemia (7); however, SMF is rare in lymphoid neoplasms. The present study reported a case of reversible MF associated with Hodgkin's lymphoma (HL), which was resolved following remission of lymphoma.…”
Section: Introductionmentioning
confidence: 99%